Dual-color optical activation and suppression of neurons with high temporal precision - Noëmie Mermet-Joret; Andrea Moreno; Agnieszka Zbela; Milad Nazari; Bárður Eyjólfsson Ellendersen; Raquel Comaposada Baro; Nathalie Krauth; Anne von Philipsborn; Andreas Toft Sørensen; Joaquin Piriz; John Yu-luen Lin; Sadegh Nabavi (eLife)
A well-known phenomenon in the optogenetic toolbox is that all light-gated ion channels, including red-shifted channelrhodopsins (ChRs), are activated by blue light, whereas blue-shifted ChRs are minimally responsive to longer wavelengths. Here, we took advantage of this feature to create a system which allows high-frequency activation of neurons with pulses of red light, while permitting the suppression of action potentials (APs) with millisecond precision by blue light. We achieved this by pairing an ultrafast red-shifted ChR with a blue light-sensitive anion channel of appropriately matching kinetics. This required screening several anion-selective ChRs, followed by a model-based mutagenesis strategy to optimize their kinetics and light spectra. Slice electrophysiology in the hippocampus as well as behavioral inspection of vibrissa movement demonstrate a minimal excitation from blue light. Of significant potential value, in contrast to existing tools, the system we introduce here allows high-frequency optogenetic excitation of neurons with red light, while blue light suppression of APs is confined within the duration of the light pulse.